Baicalein self‐microemulsion based on drug–phospholipid complex for the alleviation of cytokine storm. Issue 1 (20th June 2022) - Liao, Hengfeng; Ye, Jun; Gao, Yue; Lian, Chunfang; Liu, Lu; Xu, Xiaoyan; Feng, Yu; Yang, Yanfang; Yang, Yuqi; Shen, Qiqi; Gao, Lili; Liu, Zhihua; et al.
Abstract: Cytokine storm is a phenomenon whereby the overreaction of the human immune system leads to the release of inflammatory cytokines, which can lead to multiple organ dysfunction syndrome. At present, the existing drugs for the treatment of cytokine storm have limited efficacy and severe adverse effects. Here, we report a lymphatic targeting self‐microemulsifying drug delivery system containing baicalein to effectively inhibit cytokine storm. Baicalein self‐microemulsion with phospholipid complex as an intermediate carrier (BAPC‐SME) prepared in this study could be spontaneously emulsified to form 12‐nm oil‐in‐water nanoemulsion after administration. And then BAPC‐SME underwent uptake by enterocyte through endocytosis mediated by lipid valve and clathrin, and had obvious characteristics of mesenteric lymph node targeting distribution. Oral administration of BAPC‐SME could significantly inhibit the increase in plasma levels of 14 cytokines: TNF‐α, IL‐6, IFN‐γ, MCP‐1, IL‐17A, IL‐27, IL‐1α, GM‐CSF, MIG, IFN‐β, IL‐12, MIP‐3α, IL‐23, and RANTES in mice experiencing systemic cytokine storm. BAPC‐SME could also significantly improve the pathological injury and inflammatory cell infiltration of lung tissue in mice experiencing local cytokine storm. This study does not only provide a new lymphatic targeted drug delivery strategy for the treatment of cytokine storm but also has great practical significance for the clinical development of baicalein self‐microemulsion therapies for cytokine storm.